Arabidopsis Circadian Clock Repress Phytochrome a Signaling - Liu, Yang; Sun, Yanzhao; Yao, Heng; Zheng, Yanyan; Cao, Shuyuan; Wang, Haiyang (Frontiers in Plant Science, 2022)
The plants’ internal circadian clock can strongly influence phytochrome signaling in response to the changes in the external light environment. Phytochrome A (phyA) is the primary photoreceptor that mediates various far-red (FR) light responses. phyA signaling is modulated by FHY3 and FAR1, which directly activate the transcription of FHY1 and FHL, whose products are essential for light-induced phyA nuclear accumulation and subsequent light responses. However, the mechanisms by which the clock regulates phyA signaling are poorly understood. Here, we discovered that FHY1 expression is diurnally regulated, peaking in the middle of the day. Two Arabidopsis core clock components, CIRCADIAN CLOCK ASSOCIATED1 (CCA1) and TIMING OF CAB EXPRESSION1 (TOC1), repress FHY3/FAR1-mediated FHY1/FHL activation. Consistently, the specific expression pattern of FHY1 under diurnal conditions is altered in cca1-1, toc1-101, CCA1 and TOC1 overexpression plants. Furthermore, far-red induced gene expression and particularly nuclear accumulation of phyA are compromised in TOC1 and CCA1 overexpression seedlings. Our study revealed a previously unidentified FHY1 expression pattern in diurnal cycles and is negatively regulated by CCA1 and TOC1.